The Affecting Factors and Overcoming Strategies of Reading Aloud Anxiety at the Eighth Grade of MTSN 2 Merangin - Lasturah; Roza Anggraini (EduInovasi: Journal of Basic Educational Studies, 2024)
This study examines the factors contributing to reading aloud anxiety among eighth-grade students at MTSN 2 Merangin and proposes effective strategies to mitigate these anxieties. Key factors identified include fear of making mistakes, shyness, lack of confidence, fear of ridicule, and a perceived lack of ability in vocabulary, motivation, preparation, and grammar. To address these issues, various strategies were implemented: providing additional practice and constructive feedback, fostering positive thinking, creating a supportive and non-judgmental classroom environment, encouraging peer support through group activities, and incorporating games and interactive exercises. Data was collected through classroom observations, student and teacher interviews, and pre- and post-intervention surveys. Analysis showed significant improvements in students' confidence and participation in reading aloud activities. By understanding and addressing the root causes of anxiety, educators can create a more conducive learning environment that encourages active participation and enhances students' reading skills. This research highlights the importance of targeted interventions and supportive teaching practices in reducing reading aloud anxiety and improving overall student performance.